Analisis Overall Equipment Effectiveness (OEE) untuk Meningkatkan Kinerja Operasional pada Queen Laundry - Rahmatunisa Zahrah; Masduki Asbari (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
This study aims to analyze the effectiveness of laundry machines at Queen Laundry using the Overall Equipment Effectiveness (OEE) method. A quantitative case study approach was employed by collecting data on operating time, downtime, production output, and defective products. The results indicate an OEE value of 83%, which is below the world-class standard of 85%, with availability at 85%, performance at 100%, and quality at 98%. The main factor contributing to reduced effectiveness is low availability due to machine downtime. The Six Big Losses analysis reveals that breakdown losses, idling and minor stoppages, reduced speed losses, and process defect losses are the dominant causes. The novelty of this study lies in the integrated application of OEE and Six Big Losses in a small-scale laundry industry to identify specific inefficiency sources. These findings highlight the importance of improving maintenance practices to enhance operational performance.